1996
DOI: 10.1128/jcm.34.3.717-719.1996
|View full text |Cite
|
Sign up to set email alerts
|

Controlled study of cytolethal distending toxin-producing Escherichia coli infections in Bangladeshi children

Abstract: The role of cytolethal distending toxin (CDT)-producing Escherichia coli, a newly described category of E. coli, in the causation of diarrhea was studied by screening E. coli isolates from 546 children <5 years of age with diarrhea and 215 matched controls without diarrhea by using a specific DNA probe. Although CDTpositive E. coli strains were isolated from more children with diarrhea than from healthy controls (3.1 versus 0.93%), this difference did not reach statistical significance (P ‫؍‬ 0.082). All CDT-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…The CDTproducing bacteria belonged to different genera and were isolated from patients or animals with numerous types of disease (Johnson and Lior, 1988a,b). In a recent study, the production of CDT by E. coli in Bangladeshi children with or without diarrhoea showed that there was no statistically significant difference in the isolation rate of CDTþ E. coli between the two groups (Albert et al, 1996). Nevertheless, animal assays may implicate CDT in the pathogenesis of colibacillosis.…”
Section: Discussionmentioning
confidence: 99%
“…The CDTproducing bacteria belonged to different genera and were isolated from patients or animals with numerous types of disease (Johnson and Lior, 1988a,b). In a recent study, the production of CDT by E. coli in Bangladeshi children with or without diarrhoea showed that there was no statistically significant difference in the isolation rate of CDTþ E. coli between the two groups (Albert et al, 1996). Nevertheless, animal assays may implicate CDT in the pathogenesis of colibacillosis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, DEC has been divided into at least six groups based on the presence of chromosomal and plasmidencoded virulence genes, such as EPEC, ETEC, EIEC, EHEC, EAEC and diffusely adherent E. coli (DAEC) (46). However, CTEC has not yet been proved to belong to any particular category of DEC, although a number of CTEC strains have been isolated from diarrheal patients in several countries (27)(28)(29)(30)(31)(32)(33). Various types of cdt genes were detected in EPEC (27,28,30,47), EAEC (23,27), ETEC (47) and EHEC (20,38,41,47).…”
Section: Discussionmentioning
confidence: 99%
“…CTEC have been isolated from pediatric patients with diarrhea in several countries including India, Bangladesh, Nigeria and Brazil (27)(28)(29)(30)(31)(32)(33), although its epidemiological significance is not established (27,32). However, studies in animal models indicated that CDT is involved in diarrhea and an inflammatory response (34)(35)(36).…”
mentioning
confidence: 99%
“…In Bangladesh, many infants and young children develop diarrhea due to infection with E. coli (16,17). Previous studies have mainly focused on E. coli strains of clinical origin commonly belonging to the ETEC, EPEC, and EAEC or DAEC categories (2,3,18). EIEC has not been detected in Bangladesh nor has any EHEC been isolated from clinical specimens from this country (3).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids also carry genes for antimicrobial resistance, sequestering, and utilization of substrates and mobilization of plasmid themselves between strains, species, and genera (15). Studies carried out so far have largely focused on E. coli strains of clinical origin (2,3). Despite being part of the normal intestinal flora (11), E. coli is found in aquatic ecosystems physically isolated from any source of fecal contamination (1).…”
mentioning
confidence: 99%